A Feminist Poststructuralist Critique of Talent Management: Toward a more Gender Sensitive Body of Knowledge. Issue 3 (July 2019) - Makarem, Yasmeen; Metcalfe, Beverly Dawn; Afiouni, Fida
The field of talent management (TM) has grown over the last two decades, and much theoretical and methodological progress has been made in an effort to better conceptualize the field. Despite these efforts, the construction of knowledge within TM research has ignored power and gender dynamics. In this paper, we adopt a feminist poststructuralist perspective and unveil how talent management theory is underpinned by predominant masculinist discourses that create and sustain business elites in a neoliberal world order. Based on a textual and discourse analysis of foundational texts on TM, we identify the power effects of language in shaping current TM theory. This study raises questions concerning the epistemological foundations of talent management as objective, neutral, and observable. We suggest that future researchers adopt critical methods of inquiry to ensure that gender and equity issues are interrogated within dominant talent management writings.